2018
DOI: 10.1002/ags3.12213
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of neoadjuvant chemoradiotherapy in rectal cancer: Future treatment perspectives

Abstract: Neoadjuvant chemoradiotherapy (nCRT) has been widely used as a multidisciplinary approach for stage II/III rectal cancer. However, its safety and efficacy are controversial because previous studies have shown conflicting outcomes. The present review aimed to elucidate the benefits and limitations of nCRT for patients with rectal cancer. Future perspectives of nCRT are also described. No recent randomized trials have been able to show a survival benefit, although many studies have demonstrated good local contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…Cancer tissue specimens were obtained from a consecutive series of 342 patients who underwent curative resections for CRC at the Department of Gastroenterological, Breast and Endocrine Surgery, Yamaguchi University Graduate School of Medicine, Japan, from 1993 to 2012. Patients with a tumour below the peritoneal reflection were excluded from the study to exclude lower rectal cancer patients, whose preoperative treatment as neoadjuvant chemo-(radiation) therapy has been differ from colon cancer upper the peritoneal reflection, 27 and those who died from other diseases or stopped follow-up within 5 years after resection were excluded to determine the 5-year disease-specific survival (DSS) and relapse-free survival (RFS). The patient demographics and baseline characteristics are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer tissue specimens were obtained from a consecutive series of 342 patients who underwent curative resections for CRC at the Department of Gastroenterological, Breast and Endocrine Surgery, Yamaguchi University Graduate School of Medicine, Japan, from 1993 to 2012. Patients with a tumour below the peritoneal reflection were excluded from the study to exclude lower rectal cancer patients, whose preoperative treatment as neoadjuvant chemo-(radiation) therapy has been differ from colon cancer upper the peritoneal reflection, 27 and those who died from other diseases or stopped follow-up within 5 years after resection were excluded to determine the 5-year disease-specific survival (DSS) and relapse-free survival (RFS). The patient demographics and baseline characteristics are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In their research, tumors with KRAS codon 13 mutations didn't achieve pCR and also had a higher incidence of the TP53 mutation compared with tumors with other KRAS mutations. These results suggested that mutations in different KRAS codons may have different effects on the resistance of rectal cancer to nCRT and that the rectal cancers carrying TP53 and KRAS mutations have a lower opportunity to respond to nCRT compared with wild-type tumors [83,112].…”
Section: Tissue-based Tumor Molecular Biomarkersmentioning
confidence: 99%
“…Thus far, the optimal interval is considered to be 6-8 weeks. The rationale for this interval is that it is expected to increase the pCR rate and reduce postoperative complications [82][83][84].…”
Section: Interval To the Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, considering that the majority of patients will not respond to NCRT, it is extremely important to identify these patients, in an attempt to optimize the response to these patients. As there are no randomized phase-III studies to date, comparing this strategy with isolated induction chemoradiotherapy, it becomes fundamental to identify a biomarker capable of selecting patients for these approach [12,13,14].…”
Section: Introductionmentioning
confidence: 99%